Management of Cyber Security Processes as a Factor of Ensuring National and International Stability - Batirov Farhad Avazovich (Zien Journals, 2022)
The article deals with the problems of the development of the information society. Modern cybersecurity management processes are identified, the subjects of these processes and their features are identified. Cyber threats are presented as destructive events in the information and communication environment that undermine information security at the international, regional and national levels. It has been determined that ensuring cyber security and creating means of conducting modern cyber wars are priority areas of state policy in the field of national security. The author notes that it is very difficult for the world community to come to an agreement on a number of fundamentally important issues of political and legal support of cybersecurity and to develop common approaches, which is due to ideological, political and religious differences.
Keywords: cybersecurity; digital space; cybercrime; digitalization